A Bacterial Surface Display System Expressing Cleavable Capsid Proteins of Human Norovirus: A Novel System to Discover Candidate Receptors - Xu, Qian; Ni, Pei’en; Liu, Danlei; Yin, Yujie; Li, Qianqian; Zhang, Jvmei; Wu, Qingping; Tian, Peng; Shi, Xianming; Wang, Dapeng (Frontiers in Microbiology, 2017)
Human noroviruses (HuNoVs) are the dominant cause of food-borne outbreaks of acute gastroenteritis. However, fundamental researches on HuNoVs, such as identification of viral receptors have been limited by the currently immature system to culture HuNoVs and the lack of efficient small animal models. Previously, we demonstrated that the recombinant protruding domain (P domain) of HuNoVs capsid proteins were successfully anchored on the surface of Escherichia coli BL21 cells after the bacteria were transformed with a plasmid expressing HuNoVs P protein fused with bacterial transmembrane anchor protein. The cell-surface-displayed P proteins could specifically recognize and bind to histo-blood group antigens (HBGAs, receptors of HuNoVs). In this study, an upgraded bacterial surface displayed system was developed as a new platform to discover candidate receptors of HuNoVs. A thrombin-susceptible “linker” sequence was added between the sequences of bacterial transmembrane anchor protein and P domain of HuNoV (GII.4) capsid protein in a plasmid that displays the functional P proteins on the surface of bacteria. In this new system, the surface-displayed HuNoV P proteins could be released by thrombin treatment. The released P proteins self-assembled into small particles, which were visualized by electron microscopy. The bacteria with the surface-displayed P proteins were incubated with pig stomach mucin which contained HBGAs. The bacteria-HuNoV P proteins-HBGAs complex could be collected by low speed centrifugation. The HuNoV P proteins-HBGAs complex was then separated from the recombinant bacterial surface by thrombin treatment. The released viral receptor was confirmed by using the monoclonal antibody against type A HBGA. It demonstrated that the new system was able to capture and easily isolate receptors of HuNoVs. This new strategy provides an alternative, easier approach for isolating unknown receptors / ligands of HuNoVs from different samples including mammalian cell lines, oysters, and fresh produce.